Kontribusi Manajemen Hubungan Masyarakat terhadap Pelaksanaan Program Magang Mahasiswa Sebagai Implementasi Kurikulum KKNI 4.0 - Hardiansyah, Hardiansyah; Wibawa, Restu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to find out the management of public relations (PR) towards the implementation of student internships as an implementation of the KKNI 4.0 curriculum. This research is a qualitative descriptive research. The data collection techniques used in this study are semi-structured interviews, documentation and observation. The data analysis in this study used miles & huberman analysis model. Analysis consists of three flow of activities, namely data reduction, data presentation and conclusion/verification. The results of the study obtained 2 main aspects in the contribution of public relations management to the implementation of student internship programs, namely the public relations aspect by the Public Relations Bureau and aspects of the curriculum by the head of the study program. Both aspects are the main capital for universities to determine the success of student internship programs. In conclusion, the contribution of public relations management by the public relations bureau together with the study program in the student internship program has been good, so that the implementation of internship activities with related stakeholders runs smoothly. Keywords: Public Relations Management, Student Internship Program